Cultural adaptation of an evidence-based lifestyle intervention for diabetes prevention in Chinese women at risk for diabetes: results of a randomized trial. Issue 5 (13th February 2018) - Yin, Zenong; Perry, Judith; Duan, Xiaoqin; He, Meizi; Johnson, Ryan; Feng, Yanling; Strand, Mark
Abstract: Background: The prevalence of both obesity and type 2 diabetes has been on the rise in China. This randomized controlled trial was conducted to test the feasibility and effectiveness of an evidence-based diabetes prevention program in Yuci, Shanxi Province, China from 2012 to 2014. Methods: Women with pre-diabetes, ages 25–65 y, were assigned randomly to a comparison (n=75) or 6-mo lifestyle intervention condition (n=109). Weight, fasting glucose, hemoglobin A1c and self-reported diet and physical activity were measured at baseline, 6 mo and 12 mo. Results: All measures except fasting glucose improved favorably in both comparison and intervention participants at the 6- and 12-mo follow-ups. Participants in the intervention group lost more weight (−0.91 kg, p<0.05) and had a lower body mass index (−0.39 kg/m 2, p<0.05) than the comparison group at follow-up. A total of 31.6% (31/98) and 16.2% (11/68) of the participants in the intervention and comparison groups, respectively, achieved the weight loss goal of 5% at follow-up. There was no significant group difference in outcome measures at the 12-mo follow-up. Participants in the intervention group also showed favorable changes in self-reported diet and physical activity measures. Conclusions: A lifestyle intervention to prevent diabetes in at-risk women in community health centers in China is feasible and acceptable but effect sizes were small.